Late effects in survivors of childhood acute lymphoblastic leukemia: A study from Thai Pediatric Oncology Group - Pakakasama S. (2017)
Survivors of childhood acute lymphoblastic leukemia (ALL) are at risk of long-term late effects. Therefore, systematic screenings of the late complications are essential. The objective of this study was to determine the prevalence of late effects of Thai children and adolescents after completion of ALL therapy. We performed a cross-sectional study for evaluation of the late effects in ALL survivors who came for follow-up at 10 pediatric oncology centers in Thailand. We evaluated the treatment-related late complications of children and adolescents who had finished ALL treatment for at least 2 years. Demographic data, treatment modalities, and late effects were recorded and analyzed. There were 258 survivors with a median age of 12.2 years (range 3.6-23.3 years). The median follow-up time was 7.2 years (range 2-17.5 years). Forty-seven percent (122 cases) suffered from at least one late effect. Overweight/obesity was the most common late effect. Radiation of central nervous system was a significant risk factor for overweight/obesity (OR 1.97, 95% CI 1.02-3.81) and educational problems (OR 4.3, 95% CI 1.32-14.02). Our data have demonstrated a significant prevalence of late effects after childhood ALL therapy. A long-term follow-up program for survivors of childhood cancer is therefore needed in our country. © 2010 The Japanese Society of Hematology.